Acquired arteriovenous fistula associated with traumatic oroantral fistula: Endovascular treatment. Issue 5 (31st January 2012) - Sanborn, Matthew R.; Nasrallah, Ilya; Stanton, David C.; Stiefel, Michael F.; Hurst, Robert W.; Pukenas, Bryan A.; Irish, Jonathan
Abstract Background. Oroantral fistulas are pathologic connections between the oral cavity and the maxillary sinus. Arteriovenous fistulas are abnormal connections between an artery and a vein with no intervening capillary network. Methods We present an extremely rare case of barotrauma‐related oroantral fistula with an associated arteriovenous fistula between the internal maxillary artery and the ophthalmic venous system. Results The patient developed an oroantral fistula from barometric pressure changes in the setting of sinusitis. After closure and revision of the oroantral fistula, he developed proptosis and chemosis. Angiography revealed an arteriovenous fistula between the internal maxillary artery and the ophthalmic venous drainage system in the area of the oroantral fistula, which was treated with endovascular embolization. Conclusions Arteriovenous fistulas may accompany oroantral fistulas created by trauma or surgery and should be considered in patients presenting with chemosis and proptosis. Treatment with embolization should be performed before surgical intervention. © 2012 Wiley Periodicals, Inc. Head Neck, 2013